COMPARISON BETWEEN GREEN’S FUNCTION AND FINITE ELEMENT FORMULATION FOR THE LINEAR DYNAMIC OF PIPELINE CONVEYING FLUID ON WINKLER FOUNDATION - FONG, KAH SOON (2019)
Pipeline damage due to internal flow induced vibration is known to pose challenging problems in oil and gas industry. To reduce these problems, it is necessary to understand the vibration characteristics of the pipeline conveying fluid. The Winkler foundation is reported to have a stabilizing effect to the pipeline structure in the literature.